A simple method for detection of mitochondrial DNA polymorphisms - B. D. Wingfield; T. C. Harrington; J. Steimel (Fungal Genetics Reports, 1996)
Polymorphisms were identified in mtDNA of Heterobasidion annosum by digesting total genomic DNA with HaeIII, CfoI, or MspI, which recognize the restriction sites GGCC, GCGC, and CCGG, respectively. Most DNA was digested to fragments of less than 2 kb, while AT-rich fragments of 1.7 to 17 kb stood out as bands of uniform intensity after ethidium bromide staining. These fragments hybridized to mtDNA probes and were inherited in a uniparental fashion.